Research priority setting in UK podiatric surgery - Lesley Posmyk; Robyn L. Carter‐Wale; Kerry Clark; Lorna Donson; Jill Halstead; Natalie Lennox; Helen Milnes (Journal of Foot and Ankle Research, 2023)
Abstract Evidence‐based practice provides the foundation for high quality patient care, and in the NHS, research is seen as vital to enable service transformation and improve outcomes. Research is one of the four pillars of enhanced and advanced clinical practice and is therefore a fundamental part of podiatric surgery services. In order to meet the UK health research strategies, the most recent being ‘Saving and Improving Lives: The Future of UK Clinical Research Delivery’ (2021), the Faculty of Podiatric Surgery in the UK agreed to support the development of research priorities in order to inform a future research strategy. The Podiatric Surgery Research Strategy Group was set up and embarked on a project with the aim of engaging its members in formulating and agreeing national research priorities. The initial stage included a national research scoping survey to identify key themes, topic, and research questions. The final stage consisted of developing and enabling a live consensus vote conducted at the 2022 national Faculty of Podiatric Surgery Conference. At the end of the vote, the top five research topics that met the agreement criteria were: 1. Surgical treatment – forefoot, 2. Patient reported outcome measures, 3. Post‐operative management, 4. Surgical treatment – midfoot and 5. Service delivery. The top five research questions that met the criteria were1. How does quality of life improve following elective foot surgery? 2. How does podiatric surgery benefit the health of the population? 3. How does podiatric surgery benefit the health of the population in the at‐risk foot? 4. What is the most effective Lapidus fixation option? and 5. What is the benefit of utilising PASCOM‐10 to improve large scale outcome data? These will inform the initial UK podiatric surgery research priorities in the next three to five years.